Infodemic: analysis of global and local 2019-20 Coronavirus epidemic search flow. (30th September 2020) - Antinolfi, F; Brunelli, L; Cocconi, R; Brusaferro, S
Abstract: Background: The excessive amount of information (infodemic) about SARS-COV2 is a global challenge for healthcare authorities in tackling misinformation. Aim of the study was to investigate SARS-COV2 global and Italian web search amount made through a reliable information source during 2019-20 SARS-COV2 epidemic. Methods: From December 15th, 2019 to February 23rd, 2020, we used Google Trends to analyze global changes in the volume of searches about "Coronavirus" in relation to reliable sources: "World Health Organization", "WHO" and the Italian equivalents of "Ministry of Health" and "National Institute of Health". Primary searches and associated queries (AQs) were analyzed by nation and Italian Region. Results: Global interest on "Coronavirus" progressively rose from mid-January, with 2 peaks on days 28th and 31st, fell on February 20th and rose again until day 23rd. "WHO" searches fluctuated with no clear pattern but increased on January 26th and February 3rd. 'WHO' term was among the most frequent "Coronavirus" AQs and viceversa. Singapore, Italy and New Zealand were the most interested nations in "Coronavirus", while China was at first place in "Coronavirus+WHO" searches. In Italy from January 21st interest in "Coronavirus" gradually increased, with peaks on days 28th and 31st and a higher peak on February 21st. The other terms showed a fluctuating trend, with peaks on January 31st for "WHO" and "Ministry of Health" and on February 21st for all of them. "Coronavirus" was most frequently AQ to "Italy" and "China", while AQs for the other terms were "Coronavirus" and "WHO official website". The most interested Italian Regions for "Coronavirus" and "Coronavirus+WHO" were Lazio and Friuli Venezia-Giulia, respectively. Conclusions: Interest in SARS-COV2 globally increased during the considered period, especially within most affected areas. The associations between terms thus highlighted seems to confirm that the general population relies on trustworthy information sources. Key messages: Infodemic can be at the same time a danger and an opportunity during global and local health emergencies. Health systems should take advantage of current search flow in order to foster reliable information sharing.